Energy loss and theoretical uncertainties in small quark-gluon plasmas - Faraday, Coleridge (Department of Physics, 2025)
There is a wealth of evidence that a Quark Gluon Plasma (QGP) is formed in heavy-ion collisions at RHIC and the LHC. Recently, there have been observations of QGP signatures in much smaller collision systems—including proton proton, and proton heavy-ion collisions—wherein QGP was not expected to form. Experimentally measuring suppression in small systems is more difficult than in large systems, motivating the need for theoretical guidance on the problem. The goal of this thesis is to systematically improve current energy loss models, particularly in how they pertain to small systems. We present a perturbative Quantum Chromodynamics (pQCD) based energy loss model which receives small system size corrections to both the radiative and elastic energy loss, and which takes into account realistic collision geometry, production spectra, and fragmenta-tion. We use the Djordjevic-Gyulassy-Levai-Vitev (DGLV) radiative energy loss model, and include a small system size correction which adds back in previously neglected terms that are suppressed according to the system size. We find that the correction is extremely large for pions at high momenta, which leads us to question the validity of various approxima-tions in the model. We investigate the self- consistency of the various approximations used in the derivation of the Djordjevic-Gyulassy-Levai-Vitev (DGLV) radiative energy loss model, where we find that a particular approximation—the large formation time approximation—is not satisfied self-consistently within the model. We explore a kinematic cutoff on the trans-verse radiated gluon momentum, which restores the self-consistency of this approximation, but at the cost of an increased sensitivity to the exact cutoff chosen. The exploration and quantitative treatment of theoretical uncertainties in the energy loss model is a central theme of this thesis. In the same vein of uncertainty quantification, we investigate the common application of the central limit theorem to approximate the elastic energy loss as a Gaussian distribution. We find that all our results are remarkably insensitive to this approximation, not because we are in the regime of many scatters where the central limit theorem is applicable, but rather understood from an expansion of the RAA in terms of the moments of the underlying energy loss distributions. We also investigate the uncertainty in the elastic energy loss to the crossover between HTL and vacuum propagators. Finally, we perform a one-parameter fit of the strong coupling αs to available large system data from RHIC and LHC, keeping track of all of the aforementioned uncertainties. We find that the uncertainties may largely be absorbed into a different value of the strong coupling αs, but small uncertainty bands remain in any case. We explore differences in the energy loss models that remain even after the fit of the model to data, and find that the different elastic energy losses lead to different pT and system size dependencies. We also plot large-system constrained model results for small p/d/3He + A collisions, where we find that our results are quantitatively consistent with small system data from RHIC and inconsistent with small system data from LHC.